Multicultural Competence in English Language Pedagogy: An Analysis of Cultural Values in Indonesian Primary ELT Textbooks (Language Circle: Journal of Language and Literature, 2023)
This study aims at investigating how different cultures are depicted in textbooks. The textbooks were selected by examining their reference to Inner, Outer, and Expanding Circle countries, including cultural themes which represent these countries. This study’s data corpus consisted of two EFL Primary textbooks, Hang Out 4 and Hang Out 5. Employing Critical Discourse Analysis as the research design, this study adopted two frameworks to analyze the data: Kachru’s (1986) Concentric Circles to categorize the cultural contexts and Pfister and Borzelli’s (1977) categorization to identify the cultural aspects represented. The findings revealed that the cultural representation in the textbooks reflected significant diversity. Particularly within the inner circle, the United States was the nation whose culture was best represented. While in outer and expanding circles, East Asian countries were dominant and included all five categories. However, Indonesia as the source culture has little reference in this textbook.